Find, Select, Use and Re-use OER - Morgado, Lina (2015)
The Unit 2 is part of the training material "OER and Sustainability Models" (to train trainers) and it is organised in Units. With this Training Material, the learner will be able to: i) understand the approach of open movement; ii) describe/identify specific characteristics of OER; iii) find, select and use/reuse/make one OER; iii) analyse case studies of sustainable models of OER. The Unit 2 is about how to find, select and use/reuse/create an OER . Having successfully completed this Unit, the learner will be able to: a) find, select and use/reuse/create an OER . The content is an OER.